Implementation of Information Technology and Applications to Support Business Transformation of MSMEs in Makassar City - Rizal S, Muh; Mandasari, Mandasari; Adipa, Fauzan; R, Riska; Nurlaela, Nurlaela; Ramadhani, Andi Aulia (Jurnal Administrasi Bisnis, 2025)
Business transformation of MSMEs is a top priority in improving competitiveness in the digital era. This study aims to analyze the implementation of information technology and applications in supporting the transformation of MSMEs in Makassar City. The research uses a descriptive method with a quantitative approach, through a survey of 60 MSMEs that use information technology such as computers, the internet, and digital applications. Data analysis includes validity, reliability, normality, and linear regression tests to see the relationship between technology utilization and MSME performance. The results show that most MSMEs in Makassar have used information technology for administration, marketing, communication with consumers, and promotion. E-commerce proved to be an important element in expanding markets and improving operational efficiency. Statistical testing revealed a significant influence between the use of information technology and the improvement of MSME performance, including production, sales, revenue, and HR management. These findings suggest that information technology helps MSMEs in Makassar City become more competitive in the digital era.Keywords: MSMEs; Information Technology; Makassar City